Vocabulaire de l’informatique de gestion - de Villers, Marie-Eva (Assurances)

(untitled) (HEC Montréal, 1981)
The Office de la langue française has recently published an English-French, French-English vocabulary devoted to the computer and its role in modern life. Mrs. Marie-Eva de Villers, the author, in addition to providing the English or French equivalent of the various terms considered therein, has endeavoured to furnish a definition of each in order that the reader might comprehend the exact meaning of this highly specialized terminology which reflects the very complex nature of the computer world.